2021
DOI: 10.1083/jcb.202003086
|View full text |Cite
|
Sign up to set email alerts
|

The WAVE complex associates with sites of saddle membrane curvature

Abstract: How local interactions of actin regulators yield large-scale organization of cell shape and movement is not well understood. Here we investigate how the WAVE complex organizes sheet-like lamellipodia. Using super-resolution microscopy, we find that the WAVE complex forms actin-independent 230-nm-wide rings that localize to regions of saddle membrane curvature. This pattern of enrichment could explain several emergent cell behaviors, such as expanding and self-straightening lamellipodia and the ability of endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 111 publications
(208 reference statements)
6
34
0
Order By: Relevance
“…We also investigated the effect of bead-induced membrane deformation on the recruitment of other proteins that are known to sense membrane curvature–clathrin LCa ( Elkhatib et al, 2017 ; Zhao et al, 2017 ) and the WAVE complex ( Pipathsouk et al, 2021 ). Although components of CME enrich to bead-induced membrane invaginations in MDA-MB-231 cells ( Elkhatib et al, 2017 ), clathrin LCa exhibited less robust recruitment to beads than WASP in neutrophils ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also investigated the effect of bead-induced membrane deformation on the recruitment of other proteins that are known to sense membrane curvature–clathrin LCa ( Elkhatib et al, 2017 ; Zhao et al, 2017 ) and the WAVE complex ( Pipathsouk et al, 2021 ). Although components of CME enrich to bead-induced membrane invaginations in MDA-MB-231 cells ( Elkhatib et al, 2017 ), clathrin LCa exhibited less robust recruitment to beads than WASP in neutrophils ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 G ). We previously found that the WAVE complex exhibits a preference for saddle curvatures and enriches to the necks of membrane invaginations and transepithelial holes ( Pipathsouk et al, 2021 ). While the WAVE complex transiently enriched to some bead-induced invaginations, it failed to persistently enrich ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly the nucleation-promoting factor WASP co-localized with MIM at spine initiation sites to form filopodia in vitro . Recent results suggest that WAVE1 induces sheet-type actin polymerization, whereas N-WASP creates more focal point polymerization (Pipathsouk et al, 2021 ). Differential interactions of I-BAR domains with WASP may facilitate actin polymerization in dendritic filopodia whereas interactions with WASP might be needed for more organized actin structures such as spine heads.…”
Section: Introductionmentioning
confidence: 99%